Így jöttem . My Way Home - Jancsó, Miklós (MAFILM Kreatív Média Műhely, 1964)
In the final days of World War II, a young Hungarian is making his way home, through countryside full of the debris of war, when he is captured and imprisoned by Russians. Left in the custody of a young Russian soldier, the two youths form a friendship in spite of not speaking each other’s language. The Hungarian’s attempts to continue his journey homeward provide the framework for this powerful film, considered Miklós Jancsó’s first masterpiece.